Improving mathematical communication ability through problems based learning model - M Meiriyanti; S Suhendra; E Nurlaelah (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to examine the improvement of mathematical communication ability ofstudents who learn with Problem Based Learning and students who learn by Direct learning. Thisstudy is a quasi experiment with a non-equivalent control group design. The population is allstudents of class XI one of Senior High School in Indragiri Hilir regency, Riau by taking sample ofclass XI IPA 3 students as experimental group that get Problem Based Learning (PBL) and XI IPA1 as control group that get Direct learning. The problem studied is the improvement of students'mathematical communication ability. The instrument used is the test of mathematicalcommunication ability. Quantitative analysis uses the Mann-Whitney test. While qualitativeanalysis done descriptively. Based on the data analysis obtained in this study, it is found that themathematical communication ability of students who get Problem Based Learning is significantlybetter than the students who learn by direct learning.